Interrelation of Design Performance to Construction Performance - Hadri, Ferdian Al; Hidayat, Benny; Istijono, Bambang (Universitas Negeri Padang, 2024)
Planning consultant play a very important role in the success of a project, the consultant task in general is to translate the wishes and needs of the client in the design process which is poured into document drawings, structural calculations, costs, time and other supporting documents. Then supervise and provide assistance to contractors in the construction implementation phase, careful planning at the beginning of the project will produce an accurate implementation guideline product which will greatly determine the success of a project. Direct interviews were used in this study as data collection, designing questionnaires and determining variables. Questionnaires were distributed to 37 respondents and analyzed using the SEM (Structural Equation Modeling) method. The results of the analysis of the SEM method for the Interrelation of Design Performance Against Construction Performance showed that construction performance was affected by 97.3% by design and intervening performance. Human Resources is the most influential indicator in performance and design results and indicators in the design performance variables and construction performance variables are the success criteria for the design or planning document.